The Effect of NPK Fertilizer and Banana Peel Liquid Organic Fertilizer on The Growth of Red Chili (Capsicum annum L) - Desi, Petronela; Raksun, Ahmad; Mertha, I Gde; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chili plants have a high selling value when the supply of goods decreases due to late harvests in red chili centers in various regions. This can trigger Indonesian farmers to cultivate more quality chili plants because they have high economic value. This research aims to determine the effect of NPK fertilizer and banana peel liquid organic fertilizer on the growth of red chili (Capsicum annum L) and to assess the impact of the combination of NPK fertilizer and banana peel liquid organic fertilizer on red chili. This study employed an experimental approach, with data collected by assessing plant growth. NPK fertilizer had no discernible effect on the height or quantity of leaves on red chili peppers, but it did have an impact on leaf area, fresh weight, and dry weight. Red chili pepper plants' height, leaf count, leaf area, fresh weight, and dried weight were all unaffected by the application of a liquid organic fertilizer made from banana peels. Red chili pepper plant height and leaf count were not significantly impacted by the combination of NPK fertilizer and liquid organic fertilizer generated from banana peels; but, leaf area, fresh weight, and dry weight were.